2017
DOI: 10.3906/tar-1707-89
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and genetic analysis through DArTseq in common bean(Phaseolus vulgaris L.) germplasm from Turkey

Abstract: The common bean (Phaseolus vulgaris L.) is the most consumed food legume in the world and is a major source of dietary protein, carbohydrates, and valuable micronutrients, especially in developing countries. Diversity Arrays Technology (DArTseq), based on genome reduction with restriction enzymes, provides a rapid, high-throughput, and cost-effective tool capable of generating thousands of genotyped single nucleotide polymorphisms (SNPs) for a genome-wide analysis of genetic diversity. In this study, we aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 64 publications
10
13
1
Order By: Relevance
“…On average, 1,076.27 (6.89%) markers were identified per chromosome. These results are supported by earlier studies [ 32 56 58 ] reporting relatively more silicoDArT markers on common bean chromosome 2 and less number of markers on chromosome 6 [ 58 ]. However, our results made strong disagreement with Schroder et al [ 59 ], as they found maximum SNP markers on chromosome 8.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…On average, 1,076.27 (6.89%) markers were identified per chromosome. These results are supported by earlier studies [ 32 56 58 ] reporting relatively more silicoDArT markers on common bean chromosome 2 and less number of markers on chromosome 6 [ 58 ]. However, our results made strong disagreement with Schroder et al [ 59 ], as they found maximum SNP markers on chromosome 8.…”
Section: Discussionsupporting
confidence: 87%
“…According to Singh et al [ 12 ], genotypes having seed size above 40g belongs to Andean gene pool and those with seed size below 40g are called Mesoamerican gene pool accessions. The occurrence of two gene pools in Turkish bean pool were confirmed in previous studies by the Nemli et al [ 32 ]. Similarly, Nemli et al [ 32 ] along with other scientific groups also came across the prevalence of Andean gene pool in Turkey and in Europe [ 9 53 ], which strongly supports the findings in the present work.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations